2016
DOI: 10.1016/j.jad.2016.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood life events and postpartum psychosis in bipolar disorder

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…Our findings demonstrated that a greater number of early adverse life events is associated with increased risk of postpartum episodes with an observed dose–response effect, from 0 to 1 and 2 records of adversities, which has been shown for MDD in general, but rarely for postpartum psychiatric episodes (Perry et al., ). This finding was observed for any type of postpartum psychiatric as a group and by subtype of disorder, except for three or more adversities, which may be due to limited statistical power based on few observations.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings demonstrated that a greater number of early adverse life events is associated with increased risk of postpartum episodes with an observed dose–response effect, from 0 to 1 and 2 records of adversities, which has been shown for MDD in general, but rarely for postpartum psychiatric episodes (Perry et al., ). This finding was observed for any type of postpartum psychiatric as a group and by subtype of disorder, except for three or more adversities, which may be due to limited statistical power based on few observations.…”
Section: Discussionsupporting
confidence: 66%
“…Adverse childhood experiences (ACEs) have also been associated with peripartum depression (Tebeka et al, 2016) and specifically PPD (Guintivano et al, 2018;Kettunen and Hintikka, 2017;Meltzer-Brody et al, 2018;Plaza et al, 2012) in non-bipolar samples of women. This is in contrast to episodes of postpartum psychoses, for which there is little indication that ACEs influence risk of these episodes both in general population samples (Dowlatshahi and Paykel, 1990;) and as we have reported previously, specifically among women who have BD (Perry et al, 2016). Within the general population (Guintivano et al, 2018;Meltzer-Brody et al, 2018), and among those with a lifetime history of abuse (Garabedian et al, 2011), exposure to an increased number of ACEs has been demonstrated to have a cumulative effect on risk of PPD.…”
Section: Introductioncontrasting
confidence: 55%
“…History of ACEs was obtained using the BDRN Childhood Life Events Questionnaire (CLEQ, see Perry et al, 2016). The CLEQ was administered verbally to all participants following the SCAN interview once rapport had been established.…”
Section: Measurement Of Adverse Childhood Experiencesmentioning
confidence: 99%
“…These findings are consistent with evidence implicating other, predominantly biological factors in the triggering of PP early in the postpartum. While the aetiology of PP remains poorly understood and is undoubtedly complex and multifactorial, previous studies have consistently found no association between PP and psychosocial factors, such as childhood trauma and other stressful life events [9, 14, 34, 39] . Together with the data reported here, this supports a key role for underlying neurobiological mechanisms .…”
Section: Discussionmentioning
confidence: 99%